Advances in experimental methods for the elucidation of Pseudomonas syringae effector function with a focus on AvrPtoB - MUNKVOLD, KATHY R. (Blackwell Publishing Ltd, 2009)
Pseudomonas syringae infects a wide range of plant species through the use of a type III secretion system. The effector proteins injected into the plant cell through this molecular syringe serve as promoters of disease by subverting the plant immune response to the benefit of the bacteria in the intercellular space. The targets and activities of a subset of effectors have been elucidated recently. In this article, we focus on the experimental approaches that have proved most successful in probing the molecular basis of effectors, ranging from loss‐of‐function to gain‐of‐function analyses utilizing several techniques for effector delivery into plants. In particular, we highlight how these diverse approaches have been applied to the study of one effector—AvrPtoB—a multifunctional protein with the ability to suppress both effector‐triggered immunity and pathogen (or microbe)‐associated molecular pattern‐triggered immunity. Taken together, advances in this field illustrate the need for multiple experimental approaches when elucidating the function of a single effector.